Electrophysiological dysfunction induced by anti-ribosomal P protein antibodies injection into the lateral ventricle of the rat brain. (April 2017) - Gaburo, N; de Carvalho, J Freire; Timo-Iaria, C; Bueno, C; Reichlin, M; Viana, V S T; Bonfá, E
Objective: Anti-ribosomal P antibodies (anti-P) are strongly associated with neuropsychiatric lupus. This study was designed to determine whether these antibodies are capable of causing electro-oscillogram (EOSG) and behavior alterations in rats. Methods: IgG fraction anti-P positive and affinity-purified anti-P antibodies were injected intraventricularly in rats. Sequential cortical and subcortical EOSGs were analyzed during 30 days. IgG anti-Ro/SS-A and normal IgG were used as controls. Results: All 13 animals injected with IgG anti-P demonstrated a high prevalence of polyspikes, diffusely distributed in hippocampal fields and cerebral cortex. These abnormalities persisted approximately a month. Remarkably, an identical electrical disturbance was observed with the inoculation of affinity-purified anti-P antibodies. The EOSG alterations were associated with behavioral disorders with varying degrees of severity in every animal injected with anti-P. In contrast, no changes in EOSG or behavioral disturbances were observed in the control group. Conclusion: Our study indicates that anti-P antibodies can directly induce electrophysiological dysfunction in central nervous system particularly in hippocampus and cortex associated with behavior disturbances.